Transcript profiles of maize embryo sacs and preliminary identification of genes involved in the embryo sac–pollen tube interaction - Wang, Shuai Shuai; Wang, Fang; Tan, Su Jian; Wang, Ming Xiu; Sui, Na; Zhang, Xian Sheng (Frontiers in Plant Science, 2014)
The embryo sac, the female gametophyte of flowering plants, plays important roles in the pollination and fertilization process. Maize (Zea mays L.) is a model monocot, but little is known about the interactions between its embryo sac and the pollen tube. In this study, we compared the transcript profiles of mature embryo sacs, mature embryo sacs 14–16 h after pollination, and mature nucelli. Comparing the transcript profiles of the embryo sac before and after the entry of the pollen tube, we identified 3,467 differentially expressed transcripts (3,382 differentially expressed genes; DEGs). The DEGs were grouped into 22 functional categories. Among the DEGs, 221genes were induced upon the entry of the pollen tube, and many of them encoded proteins involved in RNA binding, processing, and transcription, signaling, miscellaneous enzyme family processes, and lipid metabolism processes. Genes in the DEG dataset were grouped into 17 classes in a gene ontology enrichment analysis. The DEGs included many genes encoding proteins involved in protein amino acid phosphorylation and protein ubiquitination, implying that these processes might play important roles in the embryo sac–pollen tube interaction. Additionally, our analyses indicate that the expression of 112 genes encoding cysteine-rich proteins (CRPs) is induced during pollination and fertilization. The CRPs likely regulate pollen tube guidance and embryo sac development. These results provide important information on the genes involved in the embryo sac–pollen tube interaction in maize.